2011
DOI: 10.1007/s11064-011-0410-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cocaine Increases Interleukin-1β mRNA and Immunoreactive Cells in the Cortex and Nucleus Accumbens

Abstract: The cytokine, interleukin-1β (IL1 β) is a sleep regulatory substance whose expression is enhanced in response to neuronal stimulation. In this study, IL1β mRNA and immunoreactivity (IR) are evaluated after acute cocaine. First, IL1β mRNA levels were measured at the start or end of the light period after saline or acute exposure to a low dose of cocaine (5 mg/kg, intraperitoneal (ip)). IL1β mRNA levels after an acute exposure to cocaine (5 mg/kg, ip) at dark onset were significantly higher than those obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In the brain, acute cocaine results in increased IL-1β mRNA in the NAc and cortex (Cearley et al, 2011), while methamphetamine leads to increased IL-6 and TNFα in hippocampus and frontal cortex (Gonçalves et al, 2008). Similarly, acute injections of cocaine results in elevated IL-1β mRNA in the VTA, an effect that is blocked with (+)-naloxone treatment (Northcutt et al, 2015).…”
Section: Psychostimulants Glia and Neuroimmune Signalingmentioning
confidence: 99%
“…In the brain, acute cocaine results in increased IL-1β mRNA in the NAc and cortex (Cearley et al, 2011), while methamphetamine leads to increased IL-6 and TNFα in hippocampus and frontal cortex (Gonçalves et al, 2008). Similarly, acute injections of cocaine results in elevated IL-1β mRNA in the VTA, an effect that is blocked with (+)-naloxone treatment (Northcutt et al, 2015).…”
Section: Psychostimulants Glia and Neuroimmune Signalingmentioning
confidence: 99%
“…Here, high doses of methamphetamine promote NFκB-DNA binding and induce proinflammatory cytokine gene expression. More recent studies have identified that both cocaine and methamphetamine increase proinflammatory cytokines in the nucleus accumbens, hippocampus and prefrontal cortex (Cearley et al, 2011; Gonçalves et al, 2008). Interestingly, cocaine-induced increases in IL1β were inhibited by the low-affinity TLR4 antagonist, (+)-naloxone, suggesting the involvement of the TLR4 receptor (Northcutt et al, 2015).…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…100 However, the clinical relevance of these latter findings needs further investigation. Notably, in addition to its direct inflammatory responses at BBB endothelium, cocaine administration (5 mg/kg) in rats was also shown to stimulate induction and release of proinflammatory cytokines (such as TNFa and IL-1b) in reward regions of the brain 101 that would further aggravate regional BBB damage. 43,102 Brain microglial cells that secrete a plethora of cytokines, chemokines, and other neurotoxic factors upon activation are also shown to be critical cellular targets for cocaine-induced neuroinflammation and ensuing BBB disruption.…”
Section: Cocaine Abuse and Blood-brain Barrier Impairmentmentioning
confidence: 99%